The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ani11051389
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Level of Supplemental Manganese for Yellow-Feathered Broilers during the Growth Phase

Abstract: This experiment investigated the effect of an optimized supplemental dietary manganese (Mn) on growth performance, tibial characteristics, immune function and meat quality, of yellow-feathered broilers. In three rearing periods, birds were fed for 21-d periods, from d 1 (starter), d 22 (grower) and d 43 (finisher), respectively, with basal diets (containing 16, 17, and 14 mg/kg analyzed Mn, respectively) supplemented with 0, 20, 40, 60, 80, 100, 120 and 140 mg/kg Mn. For starter phase broilers, supplemental ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The length, weight, diameter, breaking strength, or density index of tibia are usual parameters to be used for evaluating development of tibia. Studies reported that dietary supplementation of Mn as MnSO 4 , MnCO 3 , and MnO could increase the length, weight, diameter, breaking strength, and density index of tibia in broilers [ 42 , 43 , 44 ], reduce the incidence of leg abnormalities [ 25 , 32 ]. However, Bozkurt et al [ 37 ] reported that dietary supplementation of Mn as Mn-methionine and MnO with levels 12.5, 25, and 50 mg/kg has no effect on the weight, length, diameter, and density index of tibia in broilers.…”
Section: Discussionmentioning
confidence: 99%
“…The length, weight, diameter, breaking strength, or density index of tibia are usual parameters to be used for evaluating development of tibia. Studies reported that dietary supplementation of Mn as MnSO 4 , MnCO 3 , and MnO could increase the length, weight, diameter, breaking strength, and density index of tibia in broilers [ 42 , 43 , 44 ], reduce the incidence of leg abnormalities [ 25 , 32 ]. However, Bozkurt et al [ 37 ] reported that dietary supplementation of Mn as Mn-methionine and MnO with levels 12.5, 25, and 50 mg/kg has no effect on the weight, length, diameter, and density index of tibia in broilers.…”
Section: Discussionmentioning
confidence: 99%
“…In experiments with late-phase laying hens of 80 weeks of age, Nascimento et al (2014) found improvement in eggshell quality in birds fed diets supplemented with vitamin D3. Wang et al (2021) also observed an increase in the thickness of the eggshell when laying hens housed at a high density were supplemented with 25-OH-D3.…”
Section: Discussionmentioning
confidence: 77%
“…Wang et al. ( 2021 ) also observed an increase in the thickness of the eggshell when laying hens housed at a high density were supplemented with 25‐OH‐D3.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…There is an increasing pursuit of flavor in the huge chicken consumer market in China and almost half of Chinese chicken meat is from locally yellow-feathered broilers because of their good meat quality ( Gou et al, 2016 ). South China is the major production area for yellow-feathered broilers ( Wang Y. et al, 2021 ). However, South China is in tropical and subtropical regions, and heat stress (HS) has become a great challenge for yellow-feathered broiler production ( Liu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%